Odpowiedź :
Odpowiedź:
a) -66 - (-28) = -66 + 28 = -38
65 + (-84) = -19
-38 < -19
b) -(-23) = 23
-33 + 60 = 27
23 < 27
c) -55 - 17 = -72
-86 - 13 = -99
-72 > -99
d) -62 - (-35) = -62 + 35 = -27
67 + (-32) = 35
-27 < 35
Możesz zapisać sam znak (< lub >) jak chcesz, ale napisałam też obliczenie na wszelki wypadek.
Mam nadzieję, że pomogłam :>
Odpowiedź:
109.
a)
- 66 - (- 28) = - 66 + 28 = - 38
65 + (- 84) = 65 - 84 = - 19
- 66 - (- 28) < 65 + (- 28)
b)
- (- 23) = 23
- 33 + 60 = 27
- (- 23) < - 33 + 60
c)
- 55 - 17 = - 72
- 86 - 13 = - 99
- 55 - 17 > - 86 - 13
d)
- 62 - (- 35) = - 27
67 + (- 32) = 35
- 62 - (- 35) < 67 + (- 32)
Szczegółowe wyjaśnienie: